Evaluation of anterior knee pain by MRI in Erbil city, Iraqi Kurdistan Region - Azo Mohammedamin, Haveen (Zanco Journal of Medical Sciences (ZJMS), 2022)
Background and objective: Anterior knee pain is a common reason for consultation due to knee pathology among teenagers and young adults. Knowledge of the radiological appearance of the abnormalities allows a more accurate diagnosis of the cause of the pain. This study aimed to determine the causes of anterior knee pain and assess the role of MRI in evaluating cases of anterior knee pain and achieving accurate diagnosis and grading of some of the most common pathologies. Methods: This cross-sectional study included 115 patients suffering from knee joint pain, referred to the radiology department, Rizgari Teaching Hospital from the rheumatology or orthopedic outpatient clinics, or private clinics between March 2017 and January 2020. Only 34 patients had anterior knee pain. All patients underwent an MRI examination. Results: MRI examination was carried out for 34 knees of 115 patients with anterior knee pain, including 13 males (38.24%) and 21 females (61.76%). The mean age of the patients was 31 years (range 14-52 years). Most of the cases presented clinically with AKP, and four cases presented with a history of pain after trauma. Twelve cases (35.29%) had patella Alta while two cases (5.8%) had patella Baja. Trochlear dysplasia was reported in seven cases (20.58%), and type C was the most common trochlear dysplasia, which was seen in four cases out of seven (57.14%). Patellar maltracking was seen in eightcases(23.52 %), tilt of the patella in 10 cases (29.41%), and a combination of patellar tilt, Alta, and maltracking was seen in eight cases (23.52%). Six cases (17.64%) showed a combination between trochlear dysplasia, patellar tilt, and maltracking. Thirty one patients (91.17%) showed signs of patellofemoral arthrosis, and joint effusion was seen in 30 patients (88.23%). Suprapatellarplica was seen in two cases (5.40%). Conclusion: The most common cause of anterior knee pain is patellofemoral instability, either due to abnormal morphology /or joint geometry or post-traumatic, and it is occasionally caused by a serious underlying systemic disease, including inflammatory conditions and malignancies. MRI offers superior soft tissue contrast resolution and allows a more accurate evaluation of the underlying etiology.